The Problems of Self-Assessment of Children With Disabilities Through Adaptive Physical Education and Sport - G.R. Muratova (International Journal on Orange Technologies, 2021)
The article examines the psychological factors that contribute to attracting people with disabilities to adaptive physical culture and adaptive sports. Taking into account the realities caused by the global problem - the fight against the pandemic, the President and the Government of the Republic of Uzbekistan devote all their attention to strengthening the physical and mental health of the population. In this situation, the most vulnerable to the threat were people with poor health and disabled people. And the problem of rehabilitation of people with disabilities is becoming more urgent than ever